2014
DOI: 10.1016/j.jnt.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Exponential sums over points of elliptic curves

Abstract: We derive a new bound for some bilinear sums over points of an elliptic curve over a finite field. We use this bound to improve a series of previous results on various exponential sums and some arithmetic problems involving points on elliptic curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In this section, we introduce some definitions and results on exponential sums over finite fields and over elliptic curves (see [1,18,22]).…”
Section: Exponential Sumsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we introduce some definitions and results on exponential sums over finite fields and over elliptic curves (see [1,18,22]).…”
Section: Exponential Sumsmentioning
confidence: 99%
“…Then we manipulate the sums, separate some terms (a = 0) which gives 1 p k with the rest. So for a ∈ F p…”
Section: Randomness Extraction In F P Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Then given two sets A, B ⊆ Z * T , we consider the following two pair of sets Ahmadi & Shparlinski [2,3] have shown that the method of Garaev [96] and some bounds of bilinear exponential sums over points of elliptic curves, imply that at least one of the sets (3.14) and at least one of the sets (3.15) is "large". Similar arguments are used in [179] to show that for two sets P, Q ⊆ E(F q ) at least one of the sets {x(P ) + x(Q): P ∈ P, Q ∈ Q}, and {x(P ⊕ Q): P ∈ P , Q ∈ Q} , is also "large".…”
Section: Elliptic Curve Analoguesmentioning
confidence: 99%
“…For given two points P ∈ P and Q ∈ Q, the first extractor outputs the k-least significant bits of the abscissa of the point P ⊕ Q. We show that the extracted bits are indistinguishable from a random bit-string of length k. In fact, we use bilinear exponential sums, recently proposed by Ahmadi and Shparlinski [1] to bound the the statistical distance.…”
Section: Introductionmentioning
confidence: 98%